2012
DOI: 10.1002/ppul.22512
|View full text |Cite
|
Sign up to set email alerts
|

Signaling molecules in the fetal rabbit model for congenital diaphragmatic hernia

Abstract: Summary. Rationale and objectives: Little is known about molecular changes in lungs of fetal rabbits with surgically induced diaphragmatic hernia (DH). Therefore, we examined in this model gene expressions of pivotal molecules for the developing lung. Methods: At day 23 of gestation, DH was created in 12 fetuses from 4 does. Both lungs from six live DH fetuses and from six unoperated controls were harvested and weighed at term. Transcription of 15 genes involved in alveolarization, angiogenesis, regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Vukovich, et al reported both elastogenesis and transforming growth factor-β signaling were increased in DHTO to levels beyond those of DH or control (6,7). Again, our findings regarding these processes did not reach statistical significance; however their findings are consistent with the observed pattern that processes impacted by DH are excessively reversed in DHTO.…”
Section: Acknowledgmentssupporting
confidence: 82%
See 1 more Smart Citation
“…Vukovich, et al reported both elastogenesis and transforming growth factor-β signaling were increased in DHTO to levels beyond those of DH or control (6,7). Again, our findings regarding these processes did not reach statistical significance; however their findings are consistent with the observed pattern that processes impacted by DH are excessively reversed in DHTO.…”
Section: Acknowledgmentssupporting
confidence: 82%
“…While TO for CDH may gain more widespread acceptance in the coming years, there remains an urgent need to understand the cellular responses to CDH and TO so that targeted therapies may be developed to improve fetal lung development and to limit any undesirable effects of TO. There have been reports of how CDH and TO impact lung matrix synthesis (6)(7)(8)(9), lung epithelial function and surfactant (10)(11)(12)(13) and microvascular development (14)(15)(16), and that tracheal occlusion reverses some of resulting in severe pulmonary hypoplasia (2). Despite optimal medical and surgical care, mortality remains high with survivors experiencing severe restrictive lung disease and significant pulmonary hypertension (1).…”
mentioning
confidence: 99%
“…Time-dated pregnant New Zealand White rabbits were obtained at 15 days of gestational age from Charles River Laboratories (Germany) with approval by the Ethics Committee for Animal Experimentation of the District Government of Upper Bavaria (Munich, Germany; number 55.2-1-54-2531-149-08). Animals were housed as reported (63). All experiments were conducted in agreement with the Guide for the Care and Use of Laboratory Animals of the U.S. National Institutes of Health.…”
Section: Human Lung Tissuementioning
confidence: 99%
“…Due to high fetal losses and the small size of neonatal rabbit lungs, left and right lungs from each pup were differently allocated to postmortem analyses. We previously showed that biological and histological features of lung hypoplasia were also present in the right lung, i.e., contralateral to the hernia (62,63). The right upper lobe was gently expanded with 4% paraformaldehyde under vacuum and stored for 24 h at 4°C in fixative solution.…”
Section: Human Lung Tissuementioning
confidence: 99%
See 1 more Smart Citation